AL-GHAZALI'S SHARIA ETHICS FRAMEWORK IN COMMUNITY-BASED TOURISM MANAGEMENT - Widodo, Tri; Warmin; Khaerunisa, Unis; Zebua, Sukriyadin; Wahdan (jfpublisher, 2022)
This study examines the management practices of Situ Pasir Maung, a community-based tourist destination in Dago Village, Parungpanjang District, Bogor Regency, through the lens of Imam Abu Hamid Al-Ghazali's Islamic business ethics framework. As tourism intensifies globally, ensuring that tourism management aligns with Islamic ethical principles becomes increasingly critical, particularly in Muslim-majority contexts. This research addresses two principal questions: how tourism management is practically implemented at Situ Pasir Maung, and to what extent these practices conform to Al-Ghazali's ethical dimensions. Employing a qualitative descriptive approach, the study utilizes semi-structured interviews with five key informants, direct field observations, and documentation analysis to gather empirical data. The findings demonstrate substantial alignment between operational practices and Al-Ghazali's four core ethical principles: al-dunya mazra'at al-akhirah (the world as preparation for the hereafter), maslahah (social welfare), akhlaq al-karimah (moral virtue), and avoidance of riba (usury). The management exhibits integration of spiritual consciousness into daily operations through collective prayers and prohibition of un-Islamic entertainment, prioritizes community welfare through local employment and profit-sharing mechanisms, maintains moral excellence through transparent pricing and honest conduct, and adheres to Sharia-compliant financing through mudharabah and musyarakah arrangements. The study concludes that Al-Ghazali's classical ethical framework remains relevant and operationalizable in contemporary tourism management, offering a replicable model for sustainable Islamic tourism development that reconciles economic viability with ethical integrity and social responsibility.